2017
DOI: 10.22456/1679-9216.80499
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Ruminal Fluid Markers of Dairy Cows Supplemented with a Combination of Yeast Culture and Hydrolyzed Yeast

Abstract: Background: In order to reduce the effects of a negative energy balance, some measures have been taken into account in nutritional management during the transition period. The use of yeast, has been a good alternative used to improve the rumen metabolism and helping the adjustment of the microbiotato the new diet. The aim of the study was to evaluate the effects of supplementing a combination of yeast culture and hydrolyzed yeast on the metabolism of dairy cows during the transition period. Materials, Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The effect of yeast supplementation on albumin concentrations has been reported by different studies but with inconsistent results. Mumbach et al [28] observed similar serum albumin (24.7 vs. 24.8 ± 0.06) between yeast-culture-supplemented cows and control during early postpartum (from calving to 15 ± 3 DIM); however, lower albumin was observed by early lactation (15 to 18 ± 3 DIM) in yeast-culture-supplemented cows in comparison to control cows (23.1 vs. 25.6 ± 0.08). Furthermore, when compared to control cows, Faccio-Demarco et al [30] observed that transition cows supplemented with yeast culture had lower albumin levels at 3 and 7 DIM; however, this effect did not translate into an overall treatment effect.…”
Section: Inflammationmentioning
confidence: 93%
See 1 more Smart Citation
“…The effect of yeast supplementation on albumin concentrations has been reported by different studies but with inconsistent results. Mumbach et al [28] observed similar serum albumin (24.7 vs. 24.8 ± 0.06) between yeast-culture-supplemented cows and control during early postpartum (from calving to 15 ± 3 DIM); however, lower albumin was observed by early lactation (15 to 18 ± 3 DIM) in yeast-culture-supplemented cows in comparison to control cows (23.1 vs. 25.6 ± 0.08). Furthermore, when compared to control cows, Faccio-Demarco et al [30] observed that transition cows supplemented with yeast culture had lower albumin levels at 3 and 7 DIM; however, this effect did not translate into an overall treatment effect.…”
Section: Inflammationmentioning
confidence: 93%
“…Albumin is an important negative APP in ruminants, and decreased levels are correlated with an inflammatory process [27]. Moreover, albumin is commonly used as a biomarker of liver function around calving [28]. In a retrospective analysis, Bertoni et al [29] classified early lactation dairy cows based on their liver function through a liver activity index (LAI).…”
Section: Inflammationmentioning
confidence: 99%